Ambient Synthesis of One‐/Two‐Dimensional CuAgSe Ternary Nanotubes as Counter Electrodes of Quantum‐Dot‐Sensitized Solar Cells. Issue 4 (18th December 2015) - Chen, Xin Qi; Bai, Yang; Li, Zhen; Wang, Lian Zhou; Dou, Shi Xue
Abstract: One‐/two‐dimensional ternary CuAgSe nanotubes (NTs) were successfully prepared from copper selenide (Cu2− x Se) NTs at room temperature within a short reaction time by the facile cation‐exchange approach. Cation exchange leads to the transformation of the crystal structure from cubic into orthorhombic and/or tetragonal with good retention of morphology. The exchange reactions are spontaneous owing to large negative changes of the Gibbs free energy. The effects of parameters such as reaction time, precursor source, and precursor ratio on the exchange reaction were investigated. The resultant CuAgSe NTs were explored as counter electrodes (CEs) of quantum‐dot‐sensitized solar cells (QDSSCs) and achieved higher conversion efficiency ( η =5.61 %) than those of QDSSCs with the gold as the CE (3.32 %). Abstract : Metal exchange : One‐/two‐dimensional CuAgSe nanotubes are prepared from Cu2− x Se nanotubes by a cation‐exchange approach and explored as counter electrodes in quantum‐dot‐sensitized solar cells to achieve high conversion efficiency (see figure).